2021
DOI: 10.1111/pops.12787
|View full text |Cite
|
Sign up to set email alerts
|

Moral Polarization Predicts Support for Authoritarian and Progressive Strong Leaders via the Perceived Breakdown of Society

Abstract: Polarization in society may hold consequences beyond the undermining of social cohesion. Here we provide the first evidence highlighting the power of perceived moral polarization in society to drive support for strong leaders. Across two studies and four samples drawn from the United Kingdom, Australia, and the United States (N = 1,664), we found evidence linking perceived moral polarization with perceived anomie in society (defined as the perceived breakdown of social fabric and leadership) and with the rise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 46 publications
4
26
0
Order By: Relevance
“…In addition to polarization creating a lens through which people viewed and responded to COVID-19, polarization within a society may also undermine confidence that a society is capable of effectively managing and overcoming a crisis. This is consistent with work that has shown that perceived polarization leads to perceived cracks in the cohesion and functionality of a society (Crimston et al, 2021), or socalled anomie (see Teymoori et al, 2016). Anomie refers to the perceived breakdown of society across two dimensions: disintegration, which refers to the perception that the social fabric within a society is breaking down (e.g., the erosion of social trust), and dysregulation, the perception that leaders and government institutions are broken and ineffective (Teymoori et al, 2016).…”
Section: Polarization Anomie and Collective Angstsupporting
confidence: 91%
See 3 more Smart Citations
“…In addition to polarization creating a lens through which people viewed and responded to COVID-19, polarization within a society may also undermine confidence that a society is capable of effectively managing and overcoming a crisis. This is consistent with work that has shown that perceived polarization leads to perceived cracks in the cohesion and functionality of a society (Crimston et al, 2021), or socalled anomie (see Teymoori et al, 2016). Anomie refers to the perceived breakdown of society across two dimensions: disintegration, which refers to the perception that the social fabric within a society is breaking down (e.g., the erosion of social trust), and dysregulation, the perception that leaders and government institutions are broken and ineffective (Teymoori et al, 2016).…”
Section: Polarization Anomie and Collective Angstsupporting
confidence: 91%
“…However, while the current research further emphasizes the potential dangers of polarization in our societies, additional research is Looking forward, though the longitudinal component is a particular strength of the current research, as the current data is correlational in nature, we cannot make causal claims about the nature of the identified relationships which is something that might be examined in future experimental research. For example, future research could test the theorized causal links using fictional society paradigms as seen in research examining similar societal level phenomena that can be challenging to manipulate (e.g., Orinthia and Bimboola; Crimston et al, 2021;Jetten et al, 2015). In place of the COVID-19 anomie measure created for the current research, future research might examine whether the observed relationships hold beyond the COVID-19 context-i.e., using the established perceptions of anomie scale (Teymoori et al, 2016), which is not COVID specific.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, they have developed negative emotions (mistrust and grievances) against political authorities. These results thus contribute to the literature on the link between societal anomie and the expression of negative emotions [13,31,32,49,52,53].…”
Section: Discussionsupporting
confidence: 68%